Multi-UAV placements to minimize power consumption in urban environment - Cho, Jun Woo; Kim, Song; Kim, Jae Hyun (Advances in Intelligent Systems and Computing, 2019)
In this paper, we find optimal multi-Unmanned Aerial Vehicle (UAV) placements with the low power consumption of UAV in an urban environment. To solve the NP-hard problem, we use non-hierarchical method. Performance analysis shows that average power consumption of UAV according to the number of UAVs and the relationship between power consumption and capacity fairness of UAV.
Keywords: Capacity fairness; Hierarchical method; Low-power consumption; Non-hierarchical; Optimization theory; Performance analysis; Positioning; Urban environments; Non-hierarchical; Optimization theory; Positioning; Power consumption; UAV